Brief Report: HIV Testing and Risk Among Justice-Involved Youth - Haney-Caron, Emily (AIDS Behav, 2020)
Justice-involved youth have a number of risk factors for HIV infection, including high rates of substance use, psychiatric comorbidities, and risky sexual behaviors. Although detained youth are likely to receive health care—which may include HIV testing—court-involved, non-incarcerated (CINI) youth may be unlikely to receive HIV testing services either before or during their justice involvement. However, the relationship between risk factors and HIV testing among CINI youth is largely unknown. We explored the association between HIV testing and factors commonly associated with both HIV testing and HIV risk among 173 CINI youth with identified behaviors that put them at risk for HIV acquisition. Only 15.6% of participants reported a lifetime history of HIV testing, despite high rates of sexual and substance use risk behaviors. Age (older), gender (female), sexual orientation (non-heterosexual), recent marijuana use, lifetime use of other drugs, history of a sexually transmitted infection, pap smear in the past year and history of mental health/substance use treatment were all significantly associated with lifetime HIV testing. The extremely low testing rates in this sample emphasize that the juvenile justice system outside of detention is not adequately addressing youths’ needs related to HIV testing or ensuring access to testing services for youth at risk of contracting HIV. Results suggest that additional efforts are needed to connect justice-involved youth to healthcare more broadly and HIV testing in particular.